Additive manufacturing and characterization of complex Al2O3 parts based on a novel stereolithography method. Issue 5 (6th June 2017) - An, Di; Li, Hezhen; Xie, Zhipeng; Zhu, Tianbin; Luo, Xudong; Shen, Zhijian; Ma, Jing
Abstract: In this work, we prepared Al2 O3 ceramic green parts with complex geometry and architecture using an additive manufacturing process based on stereolithography. The rheological and thermal behavior of Al2 O3 slurry was firstly examined and used to establish the conditions for molding and debinding. As opposed to previous researches that only focused on manufacture techniques, the sintering behavior and densification process were systematically investigated. In addition, special attentions were paid to the evolution of microstructure between green bodies and sintered parts. The results showed that debound parts were equipped with uniform particle packing and narrow pore size distribution. The dimensions of the Al2 O3 parts changed anisotropically with the different processing steps. The densification process was greatly accelerated by the decrease in pore size and annihilating of interconnected pores in which significant grain growth was observed above 1450°C. The sintered part also had a homogeneous microstructure and no interface between adjacent layers. High densification (relative density of 99.1%) and much desirable Vickers hardness (17.9 GPa) of Al2 O3 parts were achieved at the sintering temperature of 1650°C.